Konsep Etika Profesi Keguruan dalam Perspektif Pendidikan Islam: Kajian Teoretis dan Relevansinya di Era Modern - Nur Habibah; Muhammad Sapto Murtadlo; Moh Ali (CV. ITTC INDONESIA, 2025)
This study aims to examine the concept of professional teaching ethics from the perspective of Islamic education and its relevance in addressing the challenges and dynamics of the modern era. The background of this research stems from the crucial role of teachers as professional educators, who are required not only to possess pedagogical competence but also strong moral integrity and ethical values. Employing a qualitative approach with the library research method, this study collects data through a critical review of classical and contemporary literature related to teaching ethics in Islam and the ethical challenges encountered by the teaching profession in the modern era. The findings indicate that professional teaching ethics in the Islamic educational perspective are rooted in the values of monotheism (tauhid), trustworthiness (amanah),sincerity (ikhlas),justice (‘adl), and compassion (rahmah), which are manifested in the teacher’s responsibilities toward students, society, and God (Allah SWT). In the modern context, these ethical principles remain highly relevant and are increasingly vital in addressing moral degradation, character crises, and the challenges posed by technology and globalization within the education sector. The analysis reveals that integrating Islamic ethical values into teaching practices can enhance teacher professionalism and foster the creation of a character-based and humanistic educational environment. This study recommends the internalization of Islamic ethical values within teacher education curricula and the reinforcement of moral development for educators in the digital era. Such efforts are expected to shape an education system that is more oriented toward spiritual and humanistic values, enabling educators to navigate contemporary challenges while upholding high standards of knowledge and morality.